Gay and Lesbian Applicants to the Bar: Even Lord Devlin Could Not Defend Exclusion, Circa 2000 - Finer, Joel Jay (Columbia Journal of Gender and Law, 2001)
Some months ago, the Editors of this Journal solicited an historic “Brief,” to be published anonymously (at the author’s request) -Brief Against Homophobia at the Bar: To Law School Dean: Mid 1960s, 10 Colum. J. Gender & Law 63 (2000). The present article: a) explores the numerous legal, social, and attitudinal developments since that Brief was written (in the mid-1960s); b) develops tests and criteria for evaluating the “good moral character” requirements for admission to the practice of law (particularly as impacting on sexual practices, propensities, and gender orientation, lawful or unlawful in different jurisdictions at different times); and c) relates developments in attitudes and practices of Bar examiners.